Persepsi Mahasiswa Kesehatan terhadap Interprofessional Education - Ance Ria Manalu; Rika Endah Nurhidayah (Elisabeth Health Jurnal, 2023)
Background: The success of satisfying services is obtained from the cooperation of all teams in healing patients. Services cannot be separated from teamwork where there is collaboration between other health teams. For this reason, this collaboration needs to be taught in an educational curriculum known as interprofessional education (IPE).Objective: To identify students' perceptions about IPEMethod: the research method used in this study is a study literature review. This journal is obtained from search results through Proquest, Science Direct, Google Scholar, Google Search, MDPI, Pubmed between 2019-2023Results: IPE can increase interaction between health students, can establish collaboration between professions, can improve knowledge between different professions,Conclusion: IPE can be an initial strategy to form collaboration between health students where good communication will have an impact on improving services and increasing patient satisfaction.